Serious applications of technology in games and health (2019)
Este volumen, busca principalmente motivar y visualizar los trabajos de investigadores jóvenes. Es resultado de la conferencia Edutainment 2019, la treceava conferencia internacional en e-learning y juegos y, el Workshop on Computing and Technology in Health realizado en paralelo y como evento complementario a Edutainment. This volume seeks mainly to motivate and visualize the works of young researchers. It is the result of the Edutainment 2019 conference, the thirteenth international conference in e-learning and games and, the Workshop on Computing and Technology in Health held in parallel and as a complementary event to Edutainment.